Libraries: Facilitators of Knowledge Generation - Aina, L.O. (Ghana Library Journal, 2012)
I need not describe what a library is since most of us here are librarians, but for the purpose of this paper, we must have a definition that is all inclusive. I prefer to refer to a library as “a place where print, digital and other non-print materials are collected, organized and made available for access and use". Thus, a library is expected to have materials such as printed and electronic books, printed and electronic journals, audio tapes, videotapes, maps, documents, CDs, cassettes, manuscripts, slides, microfilm, microfiche, realia, etc, and the equipment neededfor accessing the various formats of information. These materials are managed by professional librarians and other workers in the library. The library may be made of walls, where these materials are stored; or it could be virtual, where all the information needed is stored on a computer with Internet facilities, which will be accessible to its registered users. The ultimate aim of a library is to provide information, which when accessed and used could lead to knowledge generation and national development. The library is therefore best placed among other institutions to facilitate knowledge generation since the main business of a library is to provide information to its users, which is heterogeneous.